(untitled) (Revista de Ciências Agroveterinárias, 2012)
The semen quality is a determining factor for obtaining good results with reproductive biotechnologies, such as artificial insemination (AI). Thus, the evaluation of sperm parameters is essential to determine the fertility of gametes. Assessment techniques that best predict in vitro fertility of sperm have been relentlessly pursued with the purpose of ensuring better results after AI. However, until now, no evaluation methodology alone was efficient for this purpose. Then it is recommended to associate the use of these techniques to better predict the fertilizing ability of spermatozoa. In recent years a great number of new strategies were developed for semen evaluation, with the highlighted use of fluorescent probes. These techniques have limited use due to unfamiliarity with their employment. The aim of this paper is to review the advances on semen evaluation and prediction of their fertilising ability, with emphasis on those based on fluorescent probes.